Baksos Kesehatan Penduduk Pralansia & Lansia dengan Hipertensi di Rw 01 Kelurahan Tanjungrejo Kecamatan Sukun Kota Malang - Hilda Mazarina Devi; Ronasari Mahaji Putri (Jurnal Abdimas Kesehatan (JAK), 2023)
The results of a preliminary study at RT 06 RW 01 Tanjungrejo Village, Sukun District, Malang City found that 25 elderly people experience hypertension and the number of elderly people with hypertension reached 89.28% of the entire elderly population living in this area. Social service activities are carried out in the form of a series of activities: health education through poster media with the topic "Danger Signs of Hypertension", brain gym exercises, as well as screening of the elderly's diet and checking the elderly's blood pressure carried out as a form of community service, mentoring, promotive efforts and prevention of health problems in the elder population. The activity was held in October 2022 with 26 elderly participants. It can be concluded that this activity ran smoothly and received an enthusiastic response from the participants. Sustainability and continuity of activities is highly recommended to improve the health status of the elderly in the region.